1991
DOI: 10.1093/jac/27.suppl_a.61
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of clarithromycin and roxithromycin into nasal mucosa, tonsil and lung in humans

Abstract: The diffusion of clarithromycin and roxithromycin into respiratory tract tissues was studied in 174 adult patients undergoing surgery. Patients received clarithromycin 250 mg orally (500 mg in the case of lung tissue), or roxithromycin 150 mg orally, both given every 12 h, for three days with the last dose administered at different times before surgery. Clarithromycin reached peak tissue levels 4 h after administration and achieved mean peak concentrations of 8.32 mg/kg +/- 2.57 in nasal mucosa, 6.47 mg/kg +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 0 publications
2
36
0
2
Order By: Relevance
“…In one earlier study [8], the concentration of clarithromycin reached a peak in various tissues, including whole lung, 4 h after oral administration of 500 mg b.i.d. for 3 days.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In one earlier study [8], the concentration of clarithromycin reached a peak in various tissues, including whole lung, 4 h after oral administration of 500 mg b.i.d. for 3 days.…”
Section: Discussionmentioning
confidence: 88%
“…Azithromycin [16] has also been found to be concentrated in lung tissues. Roxithromycin, however, is not concentrated in lung tissues to the same extent [8]. One study in humans showed levels of clarithromycin of 17.5 mg路kg -1 in whole lung tissue with a serum level D. HONEYBOURNE ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance complicates therapeutic options for the clinician. Indeed, patients infected with multidrug-resistant M. tuberculosis must be treated for a much longer period of time than are patients infected with susceptible strains and response rates are decreased (7,9,12,19).Clarithromycin is a new, acid-stable macrolide antibiotic which has good bioavailability after oral dosing (11,15,25). Peak serum and lung clarithromycin concentrations are 2 to 4 g/ml and 17.5 g/g, respectively (11, 15).…”
mentioning
confidence: 99%
“…Clarithromycin is a new, acid-stable macrolide antibiotic which has good bioavailability after oral dosing (11,15,25). Peak serum and lung clarithromycin concentrations are 2 to 4 g/ml and 17.5 g/g, respectively (11, 15).…”
mentioning
confidence: 99%
“…The excellent tissue levels of the new macrolides, less frequent dosing, and broad spectrum activity make them ideal agents in the treatment of community-acquired bacterial respiratory infections, uncomplicated soft tissue infections, and sexually transmitted diseases (11)(12)(13)(14)(15)(16)(17). In numerous clinical trials they have been found to be as effective as the currently available oral antibiotics.…”
Section: Macrolides Available In the Unitedmentioning
confidence: 99%